(untitled) (Research, Society and Development, 2021)
Violence against women is a public health problem. The objective is to describe the incidence and profile of women victims of physical and sexual violence in the city of Cáceres - MT. Descriptive, cross-sectional study on cases of physical and sexual violence registered against women in Cáceres-MT from January to December 2018. As a data source, we used the records of occurrences from the Special Police Station for Women. (DEAM) and the Health Surveillance Secretariat through the Notifiable Diseases Information System (SINAN). There were 296 records of women who suffered some type of physical or sexual violence, of which 274 were recorded only in DEAM and 15 only in SINAN. According to DEAM, the most frequent type of violence was bodily injury (59.4%) and according to SINAN, the type of violence most suffered by women was physical violence (54.5%). Regarding the profile, the majority of women who suffered violence are brown, aged between 21 and 30 years, married or living with elementary and home education. Physical violence was the most frequent type of violence followed by sexual violence. This study points out disagreement between the records of violence against women, suggesting an important underreporting of the condition, in addition to the lack of integration in the areas of public security and health.